PERAN BRAND IMAGE MEMEDIASI PENGARUH CELEBRITY ENDORSER TERHADAP PURCHASE INTENTION - Roshan, Putu Agung Aprilia; Sudiksa, Ida Bagus (E-Jurnal Manajemen, 2019)
The purpose of this research is to know the role of brand image mediate the influence of celebrity endorser against purchase intention on a prospective consumer products lipstick Wardah. This research was conducted in Denpasar city, using a sample size as much as 108 respondents with a purposive sampling method. As for the data analysis technique used in this study is Path Analysis and accompanied by Sobel test to test the hypothesis put forward. Based on the results of research conducted, the brand image was able to mediate the celebrity endorser against purchase intention. Data of respondents are directly viewable is celebrity endorser of the positive and significant effect against brand Image; brand image is positive and significant effect against purchase intention; celebrity endorser of the positive and significant effect against purchase intention; as well as brand image are significantly able to mediate the celebrity endorser against purchase intention. Key Word : celebrity endorser , brand image , purchase intention